Effects of hyperbaric oxygen therapy on caustic esophageal injury in rats - KIYAN, GÜRSU (W B SAUNDERS CO-ELSEVIER INC, 2004)
Background/Purpose: Caustic esophageal burn is a serious problem in pediatric surgery. Even though many clinical and experimental studies had been performed, the complication rate could not be reduced to a satisfying level. In this study, the authors evaluated the effects of hyperbaric oxygen (HBO) therapy in caustic esophageal burn in-rats. Methods: Rats were divided into 4 groups, and caustic burn at the distal esophagus was created by applying 50% NaOH for 3 minutes in all groups. The first and third groups did not receive HBO therapy. HBO therapy was applied to the second group for 2 days and to the fourth group for 28 days. To evaluate the effects of short-term HBO therapy, the first 2 groups were compared for ulceration, inflammation, and submucosal vascular thrombosis after 2 days. The third and fourth groups were compared for the long-term effects of HBO therapy. Rats in these groups were killed after 28 days and compared for the collagen content, weight, and mortality rate. Results: In the second group, which received 2 days of HBO therapy, ulcer depth and vascular thrombosis were significantly lower than these in the first group (P = .022 and P = .020, respectively). The fourth group, which received 4 weeks of HBO therapy, had a significantly reduced mortality rate, weight loss, and collagen score and hydroxyproline level if compared with the third group (P = .035; P = .016; P = .028; and P = .033, respectively). Conclusions: These results indicate that HBO therapy is useful in caustic esophageal burn both in short-term and longterm use. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: hyperbaric oxygen; caustic burn; EPIDERMAL GROWTH-FACTOR; CONSERVATIVE TREATMENT; CORROSIVE STRICTURES; BURNS; CHILDREN; MANAGEMENT; CHILDHOOD